Modeling Risk Management for Resources and Environment in China - Wu, Desheng Dash.; Zhou, Yong.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg Imprint: Springer, 2011)
This edited volume expands the scope of risk management beyond finance to include resources and environment issues in China. It presents the state-of-the-art approaches of using risk management to effectively manage resources and environment. Both case studies and theoretical methodologies are discussed.
pt. 1. Risk management in sustainable economy -- pt. 2. Risk management in engineering projects -- pt. 3. Risk management in sustainable enterprise -- pt. 4. Environmental risk management -- pt. 5. Case study of risk management -- pt. 6. Energy risk management -- pt. 7. Risk management modeling
Electronic reproduction.
Keywords: Risk management -- China; Natural resources -- China; Economic development -- China; Environmental management -- China; Environmental risk assessment -- China